If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3 + -2i)(x + 3 + 2i) = 0 Reorder the terms: (-3 + -2i + x)(x + 3 + 2i) = 0 Reorder the terms: (-3 + -2i + x)(3 + 2i + x) = 0 Multiply (-3 + -2i + x) * (3 + 2i + x) (-3(3 + 2i + x) + -2i * (3 + 2i + x) + x(3 + 2i + x)) = 0 ((3 * -3 + 2i * -3 + x * -3) + -2i * (3 + 2i + x) + x(3 + 2i + x)) = 0 ((-9 + -6i + -3x) + -2i * (3 + 2i + x) + x(3 + 2i + x)) = 0 (-9 + -6i + -3x + (3 * -2i + 2i * -2i + x * -2i) + x(3 + 2i + x)) = 0 Reorder the terms: (-9 + -6i + -3x + (-6i + -2ix + -4i2) + x(3 + 2i + x)) = 0 (-9 + -6i + -3x + (-6i + -2ix + -4i2) + x(3 + 2i + x)) = 0 (-9 + -6i + -3x + -6i + -2ix + -4i2 + (3 * x + 2i * x + x * x)) = 0 Reorder the terms: (-9 + -6i + -3x + -6i + -2ix + -4i2 + (2ix + 3x + x2)) = 0 (-9 + -6i + -3x + -6i + -2ix + -4i2 + (2ix + 3x + x2)) = 0 Reorder the terms: (-9 + -6i + -6i + -2ix + 2ix + -4i2 + -3x + 3x + x2) = 0 Combine like terms: -6i + -6i = -12i (-9 + -12i + -2ix + 2ix + -4i2 + -3x + 3x + x2) = 0 Combine like terms: -2ix + 2ix = 0 (-9 + -12i + 0 + -4i2 + -3x + 3x + x2) = 0 (-9 + -12i + -4i2 + -3x + 3x + x2) = 0 Combine like terms: -3x + 3x = 0 (-9 + -12i + -4i2 + 0 + x2) = 0 (-9 + -12i + -4i2 + x2) = 0 Solving -9 + -12i + -4i2 + x2 = 0 Solving for variable 'i'. The solution to this equation could not be determined.
| 4=2v-3v | | -113=6(2r-5)+1 | | 5+5y+7= | | 3p-2=31 | | -8c+6=1 | | 6X+8+3X-2=-132 | | v+9*3=8 | | -156=-6-5(6+6n) | | -210-5x=-0 | | -5x-6=-2 | | 49s^2=64 | | -8(8-x)=4/5(x-10) | | -1=5+x*6 | | 784=-4x^2+800 | | 800-300= | | P=-30t^2+450t-790 | | -4=r*20-5 | | x^2y^2-x^2= | | 8x+1=4x+3 | | -6(8x+3)-6x=90 | | 0=4+n*5 | | 4b+7= | | 2x+4x+3x+3x=360 | | 5+3n+7=3 | | 4(x-3)=6x+5-3x | | 6(J+3)=102 | | -6m-5(1+3m)=163 | | x+120=24-5x | | 2b+3c=57 | | 15=-4v-v | | -(3n-8)+2=-5(n-3)-(5-4n) | | (6-5)-(2*3-9)+2= |